ASSOCIATION BETWEEN LOW-MOLECULAR-WEIGHT HEPARIN AND UNFRACTIONATED HEPARIN THROMBOPROPHYLAXIS AND ICU LENGTH OF STAY IN CRITICALLY ILL PATIENTS WITH A WELLS SCORE >=2 - Romulus Pandapotan Sianipar; Muhammad Ihsan; Ade Winata (Pena Cendekia Insani, 2026)
Venous thromboembolism (VTE) is a major preventable complication in critically ill patients. Although low-molecular-weight heparin (LMWH) and unfractionated heparin (UFH) are widely used for thromboprophylaxis, comparative data from Indonesian ICUs remain limited. This exploratory retrospective cohort study included 49 ICU patients with Wells score ? 2 who received LMWH or UFH at Haji Adam Malik General Hospital, Indonesia, in 2021. The primary outcome was ICU length of stay (LOS). Because LOS was non-normally distributed, groups were compared using the Mann-Whitney U test, with effect size estimated by the Hodges-Lehmann (HL) median difference. Of 49 patients, 41 received UFH and 8 received LMWH. Median ICU LOS was 5 days (IQR3–11) with UFH and 4 days (IQR 2–7) with LMWH. The HL median difference was-1.0 day (95% CI-5.0 to 3.0; p = 0.288), indicating no statistically significant difference. Wide confidence intervals reflected substantial uncertainty due to the small sample size and severe group imbalance. As LOS included patients who died during ICU admission, early mortality may have shortened LOS irrespective of treatment. No significant difference in ICU LOS was detected between LMWH and UFH groups. Findings are exploratory and hypothesis-generating only; larger prospective studies with severity adjustment are needed.